Developing an Interactive Intervention Planner - A Systems Engineering Perspective. (25th September 2013) - Fabry, Thomas; Vanherpe, Liesbeth; Feral, Bruno; Braesch, Christian
Intervention planning is crucial for maintenance operations in particle accelerator environments with ionizing radiation, during which the radiation dose received by maintenance workers should be reduced to a minimum. In this context, we discuss the development of a new software tool and the entailed methodology, including the visualization aspects. The software tool integrates interactive exploration of a scene depicting an accelerator facility augmented with residual radiation level simulations, with the visualization of intervention data such as the followed trajectory and maintenance tasks. Its conception allows for future inclusion of measurements performed by mobile robotic devices. In this work, we explore the systems engineering life cycle of the development process of an interactive intervention planner, which includes the needs analysis, specification explicitation, conceptual mathematical modelling, iterative implementation, design and prototype testing and usability testing.